EL APRENDIZAJE BASADO EN PROBLEMAS Y EL TRABAJO COLABORATIVO COMO FUNDAMENTOS PARA EL DISEÑO DE CURSOS VIRTUALES. EJEMPLIFICACIÓN EN LA ASIGNATURA DE INFORMÁTICA II PARA LAS CARRERAS DE PERFIL EMPRESARIAL - Castillo Maza, Juan Victoriano (2009)
Education is a lifelong sociocultural process, intentional and systematically directed to the improvement and completion of the human being person and the improvement of conditions that benefit the development and transformation of society. The changes occurring today in the system Cuban higher education project to the development dimension that allows for the fulfillment of this social order that corresponds to education. Expanding the possibilities of access to universities has led to the expansion of new models and methods as blended learning, where the self-preparation and work independently of Students have a first-order significance, so that inclusion learning strategies and training methods become appropriate in a important part of successful blended learning. The work is oriented towards the need to promote the use of a Teaching Virtual Learning Environment (EVE/A), with the design of courses supported on this type of environment allow such strategies as Problem Based Learning and Collaborative Work in groups to respond to the needs of training, both classroom and semi-professionals in Economics and Management, and also shows the results and experiences gained in the Faculty of Economics at the University of Camagüey (UC) in the implementation and development of courses on a virtual platform that facilitates the management Information and knowledge management, to develop intelligence and achieve excellence and competitive performance of these professionals.